Comparative politicals science - Zuckerman, Alan S., 1945- (Los Angeles : Sage, 2008)
v. 1. Comparative political science : research schools and methods -- v. 2. Regime structure and change -- v. 3. Politics, economics, and society -- v. 4. Political choice and behavior : from voting to violence.